TRANSLATOR TOOLS IN SECOND LANGUAGE WRITING: THEIR IMPACT ON STUDENTS’ WRITING PERFORMANCE AND PROCESS - Tuti Tuti; Ilinawati Ilinawati; Lambertha Leli (STKIP Persada Khatulistiwa Sintang, 2023)
In recent years, advancements in technology have significantly influenced various aspects of education, including language learning and writing skills. One notable technological tool that has gained prominence is the translator tool, which offers the potential to bridge language barriers and enhance writing processes for students. This background section delves into the growing significance of translator tools in the context of writing skills development, discussing their features, benefits, and potential impact on students' writing performance and processes. Writing skills have long been recognized as a fundamental component of education, enabling individuals to effectively communicate ideas, opinions, and information. Traditionally, writing instruction has encompassed grammar, syntax, vocabulary, and organization. However, with the advent of digital tools and platforms, the landscape of writing instruction has transformed. Technology has introduced innovative ways to engage learners and support their language learning journey. Translator tools, often powered by artificial intelligence and machine learning algorithms, offer the ability to translate text from one language to another with varying degrees of accuracy. These tools have evolved from basic word-for-word translations to more sophisticated models capable of understanding context and producing coherent translations. Some of the prominent translator tools include Google Translate, DeepL, and Microsoft Translator. The integration of translator tools into writing instruction has shown potential benefits for students, particularly those learning a second language or aiming to communicate across linguistic boundaries